Analysis of UKGS program in Puskesmas Halmahera - Rieza Zulfahmi Taftazani; Lina Rismayani; Bedjo Santoso; Tri Wiyatini (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2015)
ABSTRACT Public Health Center Halmahera is one of the health centers in the city of Semarang which runs UKGS phase II program in 14 elementary school (SD) and stage III at 1 SD. UKGS in Halmahera PHC activities include counseling, mass and networking toothbrush oral health carried out only once a year, which in turn have an impact on not achieving a targeted program UKGS Ministry of Health. The government is targeting oral health conditions in 2014 as the prevalence of caries-free in one molar (M1) by 50%, the extension executed onece each quaertermester 80% SD and activities jointly undertaken toothbrush every day at school in 50% SD. Based on these data, there is a gap between the state of oral health of elementary school students in the area of PHC Halmahera Semarang against government targets.The purpose of writing this case report to analyze the problems in the health center program UKGS Halmahera.This case report was compiled using the observational method through observation of data, task analysis with the observation of the work performed by dental health workers related to UKGS activities, interviews to gather information on the implementation of the program to UKGS activities manager’s in Puskesmas Halmahera Semarang.The activity results obtained in UKGS priority issues that have not been optimized in accordance with the guidelines UKGS 2012, due to lack of dental care, especially dental nurse who is spearheading the implementing UKGS.This is in accordance with the Regulation of the Minister of Health No. 58 of 2012 that the dental nurse is authorized to conduct promotive and preventive activities including conducting UKGS.There is no UKGS operational funds from Semarang City Health Office, so that the activity is difficult to do, UKGS monitoring and evaluation activities cannot be conducted, lack of parents participants’s role and children’s motivation in dental and follow-through oral health care.The report in this case conclude that UKGS activity is unsuccessful in Halmahera Semarang Public health center affected by the lack of dental health workers, there are no UKGS operational funds, the absence of monitoring and evaluation, and the lack of participation and motivation of parents toward advanced dental care. Keywords: Dental and Oral Health Care, UKGS, Public Health Center